Sex differences in the association between Life’s Essential 8 and serum anti-aging Klotho protein levels: a cross-sectional analysis in middle-aged to older adults - Zeng, Jing; Zhang, Tingting; Yang, Yan; Wang, Jinjing; Fan, Xiaojing; Wang, Qiaomin; Wang, Xuan; Tang, Haoxian; Fang, Yi (Frontiers in Aging, 2025)
BackgroundThis study explores the association between cardiovascular health metrics (Life’s Essential 8, LE8) and serum anti-aging Klotho protein levels among American adults aged 40–79, with a focus on sex-specific differences.MethodsUtilizing data from the 2007–2016 National Health and Nutrition Examination Survey (NHANES), we applied weighted multivariable regression analyses, restricted cubic spline (RCS) modeling, and subgroup analyses to investigate the association between Life’s Essential 8 (LE8) scores—including Health Behaviors and Health Factors scores—and serum Klotho concentrations, with a focus on gender differences.ResultsOur study encompassed 9,534 participants, including 4,946 females and 4,588 males. Weighted multivariable regression analyses revealed that only females exhibited a positive association between Life’s Essential 8 (LE8) scores and serum Klotho protein levels. Specifically, a 10-point increase in LE8 scores resulted in an elevation of Klotho levels by 17.61 pg/mL (95% CI: 9.53–25.69). Similarly, a 10-point increase in Health Behaviors scores increased Klotho levels by 5.7 pg/mL (95% CI: 0.14–11.26), and a 10-point increase in Health Factors scores was associated with a rise in Klotho levels by 14.6 pg/mL (95% CI: 7.70–21.51). Sensitivity analyses showed a significant positive trend in Klotho levels correlating with improvements in cardiovascular health (CVH) levels among females (β = 72.9, 95% CI: 35.91–109.88; p for trend <0.001), consistent across both Health Behaviors and Health Factors scores. No similar trends were noted in males. In females, the dose-response relationship between LE8 scores and Health Factors scores displayed nonlinear patterns, whereas Health Behaviors scores showed linear patterns. Optimal threshold was identified at 65 for LE8 score. These results were consistent across various demographic and health statuses, emphasizing the sex-specific influence of LE8 scores on serum Klotho levels. This study underscores the importance of considering gender differences in cardiovascular health and its impact on anti-aging protein levels.ConclusionIn the present study, LE8 scores and its sub-scales were positively related to serum Klotho level in middle-aged and elderly women. This study provides new evidence of sex differences in the association between LE8 scores and serum anti-aging Klotho protein levels.